2021
DOI: 10.1038/s41531-021-00195-6
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibitors of toxic alpha-synuclein identified via cellular time-resolved FRET biosensors

Abstract: We have developed a high-throughput drug discovery platform, measuring fluorescence resonance energy transfer (FRET) with fluorescent alpha-synuclein (αSN) biosensors, to detect spontaneous pre-fibrillar oligomers in living cells. Our two αSN FRET biosensors provide complementary insight into αSN oligomerization and conformation in order to improve the success of drug discovery campaigns for the treatment of Parkinson’s disease. We measure FRET by fluorescence lifetime, rather than traditional fluorescence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 114 publications
(170 reference statements)
1
43
0
Order By: Relevance
“…High-throughput screening systems (HTS) based on the inhibition of α-Syn toxic species provide starting chemical matters for drug discovery processes, and different selection platforms are constantly providing small molecules as hit compounds for PD [18] [28,53] These molecules must be studied in the subsequent steps of drug design pipelines in order to obtain leaders for preclinical and clinical trials. Recently, Braun et al (2021) identified DMC and the bi-benzimidazole Ro 90-7501 as compounds that prevented α-Syn aggregation at nanomolar concentrations and protected SH-SY5Y cells from αSyn-induced death [18]. Of these, DMC was shown to be the most potent, was effective at a nanomolar range, and could also inhibit α-Syn Ser219 phosphorylation in a murine primary neuron assay [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High-throughput screening systems (HTS) based on the inhibition of α-Syn toxic species provide starting chemical matters for drug discovery processes, and different selection platforms are constantly providing small molecules as hit compounds for PD [18] [28,53] These molecules must be studied in the subsequent steps of drug design pipelines in order to obtain leaders for preclinical and clinical trials. Recently, Braun et al (2021) identified DMC and the bi-benzimidazole Ro 90-7501 as compounds that prevented α-Syn aggregation at nanomolar concentrations and protected SH-SY5Y cells from αSyn-induced death [18]. Of these, DMC was shown to be the most potent, was effective at a nanomolar range, and could also inhibit α-Syn Ser219 phosphorylation in a murine primary neuron assay [18].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of DMC to interfere with α-Syn amyloid-like aggregation has been previously reported [18]; however, its antibiotic activity would hinder its repositioning as a neuroprotector. To study if DDMC retained the antiaggregant property shown by its precursor DMC, we monitored the ability of both TCs to inhibit α-Syn self-assembly.…”
Section: 2- Comparative Effect Of Dmc and Ddmc On The Inhibition Of α...mentioning
confidence: 95%
See 2 more Smart Citations
“…Much effort has been focused on stabilizing SYN monomers or inhibiting oligomer formation in order to prevent aggregation [49][50][51]. For example, apomorphine, a nonselective dopamine receptor agonist utilized in PD therapy, inhibited SYN fibrillation; however, it resulted in large, toxic oligomeric species [52].…”
Section: Small Molecules Peptidesmentioning
confidence: 99%